Interactive online platforms as a means of forming digital literacy of future teachers - A. Ardeev; L. Bagdasaryan; T. Kulikova; N. Poddubnaya (Вестник Северо-Кавказского федерального университета)
The relevance of the article is due to the need to develop the digital economy of Russia, which in turn depends on the level of digital literacy of teachers who transmit their knowledge, skills and attitudes to the new generation. In this regard, the society has a social order for the training of teaching staff with a high level of digital literacy. The formation of digital literacy is a systematic and purposeful process. The paper presents the use of interactive online platforms as a means of forming and developing digital literacy of future teachers. With the help of experimental data collected in the process of working with undergraduate students, it was possible to prove the effectiveness of using interactive online platforms as a means of developing a high level of digital literacy.